Schulentwicklung Bildungspolitische Wunschvorstellung oder pädagogische Realität? - Fischer, Silke (Peter Lang International Academic Publishing Group, 2016)
This cross section study shows that school-intern further teacher training does not contribute to the achievement of objectives in the area of school development in Swiss vocational schools as it is intended by educational politics. Furthermore, it reveals that the questioned teachers do not think that school-intern further teacher training and school development influence their occupational situation in terms of lessons, occupational abilities and workday at all. Also most of them do not want any support service to implement such contents in their lessons. In consideration of these facts the lastingness and efficiency of both concepts are higly doubtful. The reasons for this outcome are diverse as this study shows. At first most examined vocational schools do not have a systematical concept of school-intern further teacher training and do not arrange their school development activities according to their superior programme. Therefore a connection between the field of school-intern further teacher training and school developement is not seen by the teachers and most of the experts. Above that both fields are in the area of responsibility of the school administration and do not involve the teaching staff. The objectives and superior programme of school development as well as measures of completed school development projects are not passed on to the teaching staff. In sum one can say that the desired development projects do not reach the teaching staff. Which is why they do not achieve the necessary reliability in order to develop the lessons of the teachers in a continuous improvement process any further.